A Rare Root Canal Configuration of Maxillary Canine: A Case Report - Kunwar, Deepa; Adhikari, Bhawana; Gautam, Vanita; Arora, Chetna; Subham, Snigdha; Tripathi, Rupam (Journal of Universal College of Medical Sciences, 2018)
To report a case of endodontic treatment of a maxillary canine in which an extra canal was located and successfully treated. Endodontic therapy is essentially a micro neurologic surgical procedure involving complete debridement and three dimensional obturation of the root canal system to obtain a fluid impervious seal. The foundation of the procedure is based on the intimate knowledge and thorough understanding of the anatomy of both the pulp chamber and the root-canal system. A tooth exhibit variations in their root canal anatomy and poses a challenge in diagnosis and treatment. In the teeth particularly with additional root canals or anatomical variations, root canals are often left untreated and that would be the main reason for unfavourable outcome of the treatment. Maxillary canine are statistically more commonly single rooted, single canal but rarely may have single root with two root canals.Journal of Universal College of Medical Sciences, Vol. 5, No. 2, 2017, Page: 53-56